2012
DOI: 10.17741/bgsf/84.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of the Vaasa Batholith in the Fennoscandian shield: Petrographic and geochemical constraints

Abstract: Editorial handling: Joonas Virtasalo The ~1.88 Ga Vaasa Batholith in western Finland is a large granitoid area (8 000 km 2) with gradational contacts against the garnet-and cordierite-bearing diatexite and metatexite migmatites of the Pohjanmaa Belt. It is located in the middle part of the Fennoscandian Shield and was formed during the Svecofennian orogeny (1.9-1.8 Ga). The Batholith area consists of porphyritic and even-grained granodiorite with smaller proportions of granite and pyroxene granitoid. The vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The belt consists of turbiditic metagraywackes, mica gneisses, and mica schists, which were formed in low-P amphibolite facies conditions (Kähkönen, 2005), and includes a prominent, 1.88-1.86 Ga multi-phase granitoid area, the Vaasa batholith ( Fig. 1; e.g., Lundqvist & Autio, 2000;Mäkitie et al, 2012). The batholith, together with the surrounding metasediments, comprises the Vaasa complex.…”
Section: Geologic Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…The belt consists of turbiditic metagraywackes, mica gneisses, and mica schists, which were formed in low-P amphibolite facies conditions (Kähkönen, 2005), and includes a prominent, 1.88-1.86 Ga multi-phase granitoid area, the Vaasa batholith ( Fig. 1; e.g., Lundqvist & Autio, 2000;Mäkitie et al, 2012). The batholith, together with the surrounding metasediments, comprises the Vaasa complex.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The batholith, together with the surrounding metasediments, comprises the Vaasa complex. The boundary between the granitoids of the Vaasa batholith and the schists of the Bothnian Belt is gradual through metatexites and diatexites (Mäkitie et al, 2012) with no observed intrusive contacts (Mäkitie et al, 1999;Mäkitie, 2001;Lehtonen et al, 2005;Sipilä et al, 2008). In fact, the boundary area is texturally, mineralogically, and geochemically continuous (Mäkitie et al, 2012).…”
Section: Geologic Settingmentioning
confidence: 99%
See 3 more Smart Citations